2022
DOI: 10.3390/nu14061191
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Current Direction of the Research on Carotenoids and Human Health? An Overview of Registered Clinical Trials

Abstract: Carotenoids have been the object of numerous observational, pre-clinical and interventional studies focused on elucidating their potential impacts on human health. However, the large heterogeneity among the trials, in terms of study duration and characteristics of participants, makes any conclusion difficult to draw. The present study aimed to explore the current carotenoid research trends by analyzing the characteristics of the registered clinical trials. A total of 193 registered trials on ClinicalTrials.gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 54 publications
0
10
0
6
Order By: Relevance
“…Carotenoids represent 40-carbon molecules found in red, yellow, and orange fruits and vegetables but also in some animal products (i.e., eggs and fish), which are widely distributed in nature. They have diverse biological functions, acting as antioxidant and anti-inflammatory agents [ 164 ]. Thus, lycopene and astaxanthin are strong antioxidants that decrease the risk of both cancer and cardiovascular diseases [ 139 ].…”
Section: Resultsmentioning
confidence: 99%
“…Carotenoids represent 40-carbon molecules found in red, yellow, and orange fruits and vegetables but also in some animal products (i.e., eggs and fish), which are widely distributed in nature. They have diverse biological functions, acting as antioxidant and anti-inflammatory agents [ 164 ]. Thus, lycopene and astaxanthin are strong antioxidants that decrease the risk of both cancer and cardiovascular diseases [ 139 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we demonstrated that the protective effects of BCX could be a result of the actions of BCX rather than its enzymatic cleavage metabolites of BCO1/BCO2. However, future human intervention studies are needed to identify role of BCO1/BCO2 genotypes in lung cancer development and establish dietary recommendations for carotenoids [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the approximately 850 types of naturally occurring carotenoids, very few of them are present in human tissues. Among these it is important to mention lutein and its stereoisomers, zeaxanthin and meso-zeaxanthin, present in the human retina [ 67 ]. It is a class of a carotenoid, named xanthophyll, that cannot be synthesized de novo in the human body, and are absorbed only through diet.…”
Section: Role Of Antioxidants and Nutraceuticals In Maintaining Eye H...mentioning
confidence: 99%